String Instruments: Plucked - Jane Beethoven; Rosanne Emery; Cliff Lenz (Music magic video library, 1991)
Viewers see and hear plucked string instruments from different parts of the world - - Hear musical styles of different cultures played on instruments as diverse as the guitar, lute, harp, balalaika, ukulele, and koto - - Discover some of the ways in which string instruments can be plucked, including some unusual contemporary techniques - - Join a banjo player as he demonstrates various playing techniques.